2014
DOI: 10.1007/s11244-014-0328-y
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Heck Arylation of Acrolein Derivatives: The Role of Cyclodextrin as Additive

Abstract: Heck arylation of acrolein dialkyl acetal with (hetero)-aryl halides in water catalyzed by solid palladium catalysts and in presence of cyclodextrins is reported. Depending on the nature of the base, either cinnamaldehyde or 3-aryl propionic ester is obtained. It was shown that the presence of cyclodextrins in the reaction media increased the reaction rate as well as the stability of the palladium species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…This newly developed system was able to catalyze the Heck, Suzuki and Sonogashira couplings in aqueous medium in moderate to excellent yields and good levels of selectivity. In a similar fashion, Djakovitch and co‐workers have also reported that RaMe‐β‐CD has a stabilizing effect over the active palladium species for the [Pd]/NaY catalyst on the Heck reaction between acrolein and iodobenzene in water [32] . Later in 2018 Bazgir and co‐workers described the preparation of β‐CD decorated with Pd NPs and the use of this material as a catalyst in the synthesis of biaryls via the Ullman, Suzuki, and Hiyama couplings in water, with β‐CD being used as a stabilizer for the Pd NPs [33] …”
Section: Cyclodextrin‐promoted Cross‐coupling Reactionsmentioning
confidence: 74%
See 1 more Smart Citation
“…This newly developed system was able to catalyze the Heck, Suzuki and Sonogashira couplings in aqueous medium in moderate to excellent yields and good levels of selectivity. In a similar fashion, Djakovitch and co‐workers have also reported that RaMe‐β‐CD has a stabilizing effect over the active palladium species for the [Pd]/NaY catalyst on the Heck reaction between acrolein and iodobenzene in water [32] . Later in 2018 Bazgir and co‐workers described the preparation of β‐CD decorated with Pd NPs and the use of this material as a catalyst in the synthesis of biaryls via the Ullman, Suzuki, and Hiyama couplings in water, with β‐CD being used as a stabilizer for the Pd NPs [33] …”
Section: Cyclodextrin‐promoted Cross‐coupling Reactionsmentioning
confidence: 74%
“…In a similar fashion, Djakovitch and coworkers have also reported that RaMe-β-CD has a stabilizing effect over the active palladium species for the [Pd]/NaY catalyst on the Heck reaction between acrolein and iodobenzene in water. [32] Later in 2018 Bazgir and co-workers described the preparation of β-CD decorated with Pd NPs and the use of this material as a catalyst in the synthesis of biaryls via the Ullman, Suzuki, and Hiyama couplings in water, with β-CD being used as a stabilizer for the Pd NPs. [33] Another pivotal work in this field was published by Liu and co-workers in 2007, who described the application of β-CDcapped Pd NPs (β-CD/Pd) as catalysts in the copper-and phosphine-free Sonogashira coupling between alkynes and aryl halides (Scheme 7).…”
Section: Pd (Nano)particles/cyclodextrins Composites As Catalystsmentioning
confidence: 99%
“…Unfortunately, Heck reactions with acrolein as starting material with palladacycles or Pd(OAc) 2 /PPh 3 as catalysts either turned out to be quite inactive for electron‐rich aryl bromides or bromobenzene often leading to unselective side reactions and polymerization due to the inherently high electrophilicity and reactivity of acrolein . To avoid these disadvantages, in the literature either the dialkyl acetal derivative is used to deactivate the Michael system and ensure synthetic handling, or the more reactive, but atom‐inefficient, aryl iodides are used instead (Scheme )…”
Section: Introductionmentioning
confidence: 99%
“…For more sustainable transformations, alternative solvents have been proposed, including ionic liquids, supercritical and deep eutectic fluids, water, and biosourced organic solvents . Concerning transition metal catalyzed synthetic chemistry, and especially C−C cross‐coupling reactions, the use of water has been reported however with several drawbacks that may hamper further developments ,. Therefore polar organic solvents have still to be considered for these specific reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Concerning transition metal catalyzed synthetic chemistry, and especially CÀ C cross-coupling reactions, the use of water has been reported however with several drawbacks that may hamper further developments. [3,4] Therefore polar organic solvents have still to be considered for these specific reactions. In the search for more environmentally friendly media, biosourced liquids have attracted peculiar interest giving very promising results.…”
Section: Introductionmentioning
confidence: 99%